2017
DOI: 10.1039/c7cc05773c
|View full text |Cite
|
Sign up to set email alerts
|

A photochromic prototype based on difurylperhydrocyclopentene with remarkable photoswitching behavior and in vivo application

Abstract: A new strategy has been developed to synthesize difurylperhydrocyclopentene derivatives. The compound displays reversible photochromism in solution and thin-film. The results show that furan is superior to thiophene in terms of strong fluorescence, higher photocyclization conversion and cyclization quantum yield, as well as better fatigue resistance. Owing to the molecule being derived absolutely from C, H, and O atoms, the compound exhibits no cytotoxicity, which enables it to potentially serve as a biodegrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In comparison with compound BTE-c, it was found that the absorption maximum of compound BFE-c was shorter about 22 nm in acetonitrile solution. But the absorption maximum of compound BFE-c red-shifted about 152 nm compared to that of reported aldehyde-based difurylperhydrocyclopentene 1 [37] at the photostationary state due to the better conjugated structure of compound BFE. The emission peak at around 547 nm for compound BFE was also observed when it was excited at 386 nm ( Figure 1B) and its emission also exhibited a good response to UV light.…”
Section: Photochromic Behaviors and Fluorescent Studiesmentioning
confidence: 68%
See 2 more Smart Citations
“…In comparison with compound BTE-c, it was found that the absorption maximum of compound BFE-c was shorter about 22 nm in acetonitrile solution. But the absorption maximum of compound BFE-c red-shifted about 152 nm compared to that of reported aldehyde-based difurylperhydrocyclopentene 1 [37] at the photostationary state due to the better conjugated structure of compound BFE. The emission peak at around 547 nm for compound BFE was also observed when it was excited at 386 nm ( Figure 1B) and its emission also exhibited a good response to UV light.…”
Section: Photochromic Behaviors and Fluorescent Studiesmentioning
confidence: 68%
“…Compound BTE showed no fluorescence due to the less flexibility of furan ring, whereas the thiophene ring affected the non-radiative process. [26,37] Impressively, the emission of compound BFE red-shifted around 75 nm relative to that of compound 1 due to the strong ICT effect derived from cyano groups to bisfurylethene core in the molecule BFE.…”
Section: Photochromic Behaviors and Fluorescent Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furan, however, would help with this dilemma and has been applied in several researches of single molecular photoswitching junctions . Apart from that, recent research on difurylperhydrocyclopentene has presented a furan based diarylethene derivative showing good emission and remarkable photoswitching performances . More interestingly, the furan based photoswitch possesses low cytotoxicity and holds a potential in photoswitchable fluorescent in vivo bioimaging reagent.…”
Section: Designing New Members For Diarylethene Familymentioning
confidence: 99%
“…1 Therefore, they have great potential in various practical applications such as data storage, optoelectronic devices, sensing, tunable self-assembly morphology, super-resolution microscopy, anti-counterfeiting materials and other fields. [2][3][4][5][6] Among the family of photochromes, including spiropyran, 7 azobenzene, 8 Schiff-base, 9 triarylethylene [10][11][12] and dithienylethene (DTE), 13,14 DTE is regarded as the shining star due to its inherent bistable characteristics and excellent recyclability. Although in-depth research has been conducted on small molecule DTE materials, 15 their poor thermal stability, inferior film-forming property and easy oxidation nature are still the key constraints; however, by introducing DTE moieties into polymers, all issues can be resolved.…”
Section: Introductionmentioning
confidence: 99%